EFFECTS OF PUBLIC PARTICIPATION ON SUSTAINABILITY OF CONSTITUENCY DEVELOPMENT FUND SPORTS PROJECTS IN MWINGI WEST CONSTITUENCY, KITUI COUNTY - Mukuri, Gladys Kalekye; Wamitu, Susan Njeri (Journal of Public Policy and Administration, 2020)
Purpose: Mwingi West Constituency has been a beneficiary of this fund, particularly in the financing of sports projects which have also stalled hence the need to establish the factors contributing to the condition. This study investigated the effects of public participation on the sustainability of the CDF sports projects in Mwingi West Constituency. Methodology: The study used descriptive research design and was conducted in Mwingi West Constituency where 101 respondents were sampled from a target population of 329 beneficiaries of CDF financed initiatives in the Constituency. Simple random sampling was utilized to get the required sample size which comprised of CDF project coordinators and managers. A questionnaire was designed, piloted, tested for reliability and validity and utilised to gather the required information. Statistical Package for Social Scientists (Version 22) was used in the data analysis process and the results were presented in tables and graphs. Findings: The data analysis indicated that Public participation was a very key factor in implementing sustainable CDF projects. It explained 73.1% (R square = 0.731) of the elements that affect sustainability of CDF funded sports projects in the area of study. Unique contributions to theory, practice and policy: Public participation should be adhered to at all CDF sports project implementation processes. The government should provide adequate funds to the sports projects to fully achieve the intended goals. The researcher recommends that other similar studies should be carried out on other projects apart from sports to widen the scope of the effects of corporate governance on sustainable CDF projects. The findings of this study continue to demonstrate validity of the arguments of agency theory. Based on the findings of this study, it is recommended that this theory may be used in future in similar studies as it provides some basic foundation of studying public participation and sustainability of public projects.